Avian Sex Determination Based on Chromo Helicase DNA-binding (CHD) Genes Using Polymerase Chain Reaction (PCR) - I Khaerunnisa; E Sari; M Ulfah; . Jakaria; C Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2013)
Several bird species are sexually monomorphic. In this case, molecular approach is an efficient method for their sex determination. The sexes of monomorphic birds can be determined by PCR amplification of the CHD genes. CHD genes are preserved within avian Z and W sex chromosomes. The objective of this research was to determine sex of 21 individuals quails, pigeons, hill myna, salmon-crested cockatoos, and yellow-crested cockatoos based on CHD genes using two pairs of primers: 2550F-2718R and P2-P8. Samples from Kampong chickens and ducks were used as controls. PCR products were screened by agarose gel electrophoresis with ethidium bromide. Results showed that 2550F and 2718R primers could be used to identify sex of Kampong chickens, quails, ducks, pigeons, hill myna, salmon-crested cockatoos, and yellow-crested cockatoos. Individuals showed double (ZW) and single (ZZ) bands were identified as females and males, respectively in Kampong chickens, quails, hill myna, salmon-crested cockatoos and yellow-crested cockatoos. Males and females in ducks and pigeons showed single band in different length of base pairs. P2 and P8 primers could be used to identify the sex of pigeons, hill myna, salmon-crested cockatoos, and yellow-crested cockatoos. All of those samples showed bouble (ZW) bands for females and single (ZZ) band for males.